Tartlicious company / Mohamad Faiz Adha Zakaria ... [et al.] - Zakaria, Mohamad Faiz Adha; Mohd Arif, Mohd Shukre Amre; Abdullah, Aishah; Ahmad, Nurfathiha; Zazali, Nurul Atiqah Zharfa; Selamat, Izzati Syahirah; Mazlan, Nooraina Hidayah (2014)
Every business has their own name and every name will bring their own meaning. Sometimes it will present the name of the family's owner. At the same time also, the name of company will bring out the background of the company that tell us how the company is created. Our companies name is "Tartlicious" which are based on partnership business. This name was chosen with the approval of all company's shareholders. "Tartlicious" is reflected to seven friends that have signed the agreement to be shareholder and build the company based on the production of tart with various flavor as the main product. Without shareholders, this company cannot be build due to the problem of capital, management team and others. The main reason of the establishment of Tartlicious is because of the demand which the people nowadays want to fry something new when they want to eat. This is due to the lifestyle of the people nowadays which want to eat something that is not so heavy but can filling. Our services are also relevant especially at the Segamat area which situated in shopping complex which is One Segamat that are strategic to attract people to buy our product. We produced various flavor of tart such as mangoes, key limes, durians and passion fruits. We make some innovations in produced our dessert based on local fruit in order to compete with existing company that produced egg tart. Our business has been registered on 1 December 2014. We choose 1 January 2015 as a business commencement, as a new beginner we fry our best to gain high profit monthly, We focused on producing dessert that contain high nutrient which are suitable for all stage of ages. In our business, we had chosen partnership as the nature of the business. The reason we choose partnership are because the ideas and knowledge among the top management can be shared and no idea will be taken for granted because the capitals are from the contribution of all shareholders and able to less the risk and reduce the liabilities of owner which it is distribute to all share holders . Lastly, for future prospect of the business our company tries to be the first choice focus on Malay halal produce. We also provide quality cakes with the greatest taste to meet customer's satisfaction and to achieve zero complaint from our customer.